ECONOMIC RIGHTS OF WOMEN UNDER SOKOTO CALIPHATE: A LESSON FOR CONTEMPORARY WOMEN IN NIGERIA - Hanafi, Murtala (Spektra: Jurnal Ilmu-ilmu Sosial, 2024)
This paper economic rights of women under the Sokoto Caliphate, a lesson for women of contemporary Nigeria, discusses the various economic activities which women engaged themselves in Sokoto without interference from the men. Rights of women have occupied prominent place in the scheme of Islamic affairs from the inception of Islamic message. It is no longer a history to state that the Prophet (S.A.W) upgraded the status of women from what is used to be and made them equal with the male gender throughout the period of his Prophet hood. Part of the rights accorded women in the early days of Islam includes economic right. This paper highlight some of the entrepreneurship which women engaged in and also challenges which they face in the caliphate before now. It also discussed are the rights enjoy by Muslim women in Sokoto. Adequate attention is devoted to the proprietary and the employment rights of women in Sokoto as well as other such challenges effecting enjoyment of rights accorded Muslim, women in Islam to cater for their economic well-being. The paper is structured into major parts starting with proprietary right of women in Islam contemporary to the economic rights of women in Nigeria. As a lesson and challenges to the cotemporary women in Nigeria. The study adopted qualitative research method where secondary sources of data were utilised and analysis as its methods of analysis.